PENGARUH PENERAPAN ENTERPRISE RESOURCE PLANNING (ERP) DALAM RANTAI PASOK PT. GARUDA - Rizni Aulia Qadri; Immanuel Zai; Jerry Jerry; William Vanders; Jovi Ong; Jason Yodiputra; Melvin Melvin; Osgood Feriady Darma Saputra (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The purpose of this research was carried out to find out how effective theapplication of corporate resource planning at PT. Garudafood. This research will beanalyzed by data collection methods. In this study the authors will discuss theimplementation of ERP on PT. Garudafood, the benefits of the ERP system for PT.garuda food, and analysis of the application of the supply chain to PT. Garudafood.The conclusion from the results of the analysis is that PT. Garudafood hassucceeded in increasing the efficiency and effectiveness of its supply chainmanagement by implementing an ERP system.Keywords : Efficiency, Effectiveness, ERP, Management, Supply Chain